Compound deletion of Fgfr3 and Fgfr4 partially rescues the Hyp mouse phenotype - Li, Hua (American Physiological Society, 2011)
Uncertainty exists regarding the physiologically relevant fibroblast growth factor (FGF) receptor (FGFR) for FGF23 in the kidney and the precise tubular segments that are targeted by FGF23. Current data suggest that FGF23 targets the FGFR1c-Klotho complex to coordinately regulate phosphate transport and 1,25-dihydroxyvitamin D [1,25(OH)(2)D] production in the proximal tubule. In studies using the Hyp mouse model, which displays FGF23-mediated hypophosphatemia and aberrant vitamin D, deletion of Fgfr3 or Fgfr4 alone failed to correct the Hyp phenotype. To determine whether FGFR1 is sufficient to mediate the renal effects of FGF23, we deleted Fgfr3 and Fgfr4 in Hyp mice, leaving intact the FGFR1 pathway by transferring compound Fgfr3/Fgfr4-null mice on the Hyp background to create wild-type (WT), Hyp, Fgfr3(−/−)/Fgfr4(−/−), and Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice. We found that deletion of Fgfr3 and Fgfr4 in Fgfr3(−/−)/Fgfr4(−/−) and Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice induced an increase in 1,25(OH)(2)D. In Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice, it partially corrected the hypophosphatemia (P(i) = 9.4 ± 0.9, 6.1 ± 0.2, 9.1 ± 0.4, and 8.0 ± 0.5 mg/dl in WT, Hyp, Fgfr3(−/−)/Fgfr4(−/−), and Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice, respectively), increased Na-phosphate cotransporter Napi2a and Napi2c and Klotho mRNA expression in the kidney, and markedly increased serum FGF23 levels (107 ± 20, 3,680 ± 284, 167 ± 22, and 18,492 ± 1,547 pg/ml in WT, Hyp, Fgfr3(−/−)/Fgfr4(−/−), and Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice, respectively), consistent with a compensatory response to the induction of end-organ resistance. Fgfr1 expression was unchanged in Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice and was not sufficient to transduce the full effects of FGF23 in Hyp/Fgfr3(−/−)/Fgfr4(−/−) mice. These studies suggest that FGFR1, FGFR3, and FGFR4 act in concert to mediate FGF23 effects on the kidney and that loss of FGFR function leads to feedback stimulation of Fgf23 expression in bone.